Waqf and its legal framework in Sri Lanka: a preliminary study - Muhammed Thabith, Muhammed Buhary; Mohamad, Nor Asiah (IIUM Press, 2021)
Waqf or religious endowment refers to an institution with the religious intention to do good acts for the benefit of the beneficiaries. However, the implementation and management of Waqf all around the world (Muslim and non-Muslim countries) have witnessed a deterioration since the fall of the Ottoman Empire. Many researchers and experts speak about the Waqf revival. In this relation, the Waqf institutions in Sri Lanka in particular, have gone through several reforms including the introduction of the ministry of Waqf. This paper examines the historical evolution as well as the status quo of Waqf governance in Sri Lanka. The study employs doctrinal analysis based on past literature as well as the laws governing Waqf. This study also explores the origin of the Waqf under Islamic law. It also discusses the application of the Waqf Act in Sri Lanka and identifies the current challenges and issues of the Waqf legal framework for the Muslim Mosques Charitable Trusts or Waqf Act (MMCTWA) in Sri Lanka. The findings reveal positive development in Waqf management, but overall awareness is necessary. The legal framework requires sustainable support and cooperation from the community, private sector, and the government